An Analysis of Gender Diversity in Top Management and Its Impact on Carbon Emission Disclosure - Ichwanul Ichsan; Muhammad Dahlan; Gia Kardina Prima Amrania (Jurnal Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study examines the impact of top management gender diversity on carbon emissions disclosure in IDX-listed companies from 2019 to 2023. Research Methodology: This quantitative study utilizes purposive sampling and panel data regression to analyze secondary data from the annual and sustainability reports of IDX-listed companies in the energy, basic materials, and primary consumer sectors (2019–2023), investigating the impact of top management gender diversity on carbon emission disclosure while controlling for firm size, sustainability committees, profitability, and managerial ownership. Results: All variables, including gender diversity, significantly impact carbon emissions disclosure when considered together. The sustainability committee shows a significant positive effect, while profitability has a significant negative effect; in contrast, gender diversity, firm size, and managerial ownership have no significant impact. Conclusions: This study concludes that while all variables simultaneously affect carbon disclosure, only the sustainability committee and profitability significantly enhance transparency, whereas gender diversity has no impact. This proves that formal governance structures are more effective in driving environmental disclosures than management demographics. These findings serve as a strategic recommendation for regulators and companies to strengthen sustainability reporting standards in Indonesia. Limitations: This study is limited to three industrial sectors, lacks qualitative depth, and has a five-year observation period that may not reflect long-term trends. Contributions: This study enriches the environmental accounting literature on emerging markets and offers policy implications for regulators regarding carbon reporting standardization and incentive schemes to accelerate national ESG adoption.